The potential for internal trade and regional integration in Africa - Alemayehu Geda Fole; Edris Hussein Seid (Journal of African Trade, 2015)
This study examines the potential for intra-Africa trade and the prospects of advancing regional economic integration through such trade. A variety of empirical models are deployed for the purpose. The analysis and model simulation results reveal the existence of significant potential for intra-Africa trade. However, realizing this potential and hence the effort to advance regional integration through intra-Africa trade is challenged by lack of complementarities of exports and imports as well as the relative competitive position of African potential export suppliers. This is the result of weak infrastructure, productivity and trade facilitation - in short, acute export supply constraint that characterizes the African export trade. This calls for an innovative approach to enhance intra-Africa trade and furthering regional integration. Addressing the challenge of export supply constraint, export competitiveness and diversification is found to be crucial. This in turn calls for policies that need to go beyond liberalization to actual realization of the potential for trade through provision of regional (multi-country) and domestic infrastructures, harmonizing macroeconomic policies, enhancing trade enabling institutions, developing trade facilitation as well as regionally focused diversification plan using the existing regional economic communities (RECs) as vehicles.
Keywords: F150; F130; 330; Intra-Africa trade potential; Gravity model; Export supply constraints; Regional integration; Africa